TCP Congestion Control: A Paradigm Shift from Reactive Loss Signals to Model-Driven and Learning-Based Control - Raj Kumar,Manoj Kumar Sah,Md Ehtashamoul Haque, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Abstract - The Transmission Control Protocol (TCP) has been central to the stability andscalability of the Internet, with its congestion control mechanism playing a pivotal role. Theearly loss-based framework, epitomized by TCP Reno’s Additive Increase Multiplicativ Decrease (AIMD) strategy